Efficacy and safety of house dust mite sublingual immunotherapy in monosensitized and polysensitized children with respiratory allergic diseases. Issue 10 (21st August 2014) - Li, Peng; Li, Qi; Huang, Zhenghua; Chen, Wenbo; Lu, Yueqian; Tian, Man
<x xml:space="preserve">Abstract</x> Background The efficacy of single‐allergen‐specific immunotherapy in polysensitized subjects is a matter of debate. This study aimed to investigate the efficacy of house dust mite (HDM) sublingual immunotherapy (SLIT) in monosensitized and polysensitized children. Methods A total of 112 children, aged 4 to 13 years old, with HDM‐induced respiratory allergic diseases were allocated to a monosensitized group (n = 56) or a polysensitized group (n = 56). Both groups were treated by standard pharmacotherapy and SLIT with Dermatophagoides farinae (American HDM) extracts for 52 weeks. Symptoms, medications, visual analogue scale (VAS), and presence of adverse events (AEs) were assessed once a month. Skin‐prick test (SPT) was done before and after treatment. After treatment, subjects in the polysensitized group who completed the study were further analyzed as subgroup 1 (n = 20) and subgroup 2 (n = 15) according to the number of coexisting allergens. Results Forty‐one subjects in the monosensitized group and 35 subjects in the polysensitized group completed the study. The global clinical parameters had significantly improved after treatment, with no significant difference between the monosensitized and polysensitized group throughout this period (all p > 0.05). The comparison among the monosensitized group, subgroup 1, and subgroup 2 indicated that there was no significant difference in symptoms scores and VAS at each scheduled follow‐up visit. There was also no significant difference in total medications score (TMS) in the monosensitized group, subgroup 1, and subgroup 2 after week 24 (all p > 0.05). No severe systemic AEs were reported. Conclusion No significant difference was observed in the clinical effects of HDM SLIT between polysensitized and monosensitized children with respiratory allergic diseases.